ACCURACY ASSESSMENT OF CENTROID COMPUTATION METHODS IN PRECISE GPS COORDINATES TRANSFORMATION PARAMETERS DETERMINATION - A CASE STUDY, GHANA - Yao Yevenyo Ziggah; Hu Youjian; Christian Amans Odutola; Tien Thanh Nguyen (European Scientific Journal, ESJ, 2013)
The concept of centroid is significant for many geo-spatial applications especially in the determination of GPS coordinate transformation parameters for transforming coordinates between two geodetic datums. It estimates centroid coordinates system which is in return used in conjunction with the coordinates to estimate the parameters. Choosing an appropriate centroid technique that produces more realistic result is of paramount interest to geospatial professionals. To achieve this, the three-dimensional similarity method known as the Veis transformation model was applied to four different centroid computation procedures to investigate and assess their accuracies and performance in precise GPS datum transformation parameters estimation within Ghana Geodetic Reference Network. In order to ascertain the precision of the derived transformation parameters from the various centroid approaches, the reference standard deviation, reference adjustment variance and the individual standard deviations of the parameters determined were used. Residual analysis using maximum negative, maximum positive, mean error and standard error was done to evaluate the performance of the centroid methods. The test of normality of residuals, deterministic model, correlation coefficient, t-test on the derived transformation parameters, t-test on the correlation coefficient and root mean square error were used to evaluate and check the adequacy of the centroid procedures. The arguments are presented in favour of a more suitable centroid strategies using root mean square (RMS) which was able to give the most precise GPS datum transformation parameters and resulting coordinate values. Thus, the RMS centroid parameters transformed GPS coordinates to local coordinates at highly significant accuracies than arithmetic mean, harmonic mean and median centroid.